Retention strategies are routinely communicated to potential trial participants but often differ from what was planned in the trial protocol: an analysis of adult participant information leaflets and their corresponding protocols - Murphy, Ellen; Gillies, Katie; Shiely, Frances (Current controlled trials in cardiovascular medicine, 2024)
Background Retaining participants in randomised controlled trials (RCTs) is challenging and trial teams are often required to use strategies to ensure retention or improve it. Other than monetary incentives, there is no requirement to disclose the use of retention strategies to the participant. Additionally, not all retention strategies are developed at the planning stage, i.e. post-funding during protocol development, but some protocols include strategies for participant retention as retention is considered and planned for early in the trial planning stage. It is yet unknown if these plans are communicated in the corresponding participant information leaflets (PILs). The purpose of our study was to determine if PILs communicate plans to promote participant retention and, if so, are these outlined in the corresponding trial protocol. Methods Ninety-two adult PILs and their 90 corresponding protocols from Clinical Trial Units (CTUs) in the UK were analysed. Directed (deductive) content analysis was used to analyse the participant retention text from the PILs. Data were presented using a narrative summary and frequencies where appropriate. Results Plans to promote participant retention were communicated in 81.5% ( n = 75/92) of PILs. Fifty-seven percent ( n = 43/75) of PILs communicated plans to use “combined strategies” to promote participant retention. The most common individual retention strategy was telling the participants that data collection for the trial would be scheduled during routine care visits (16%; n = 12/75 PILs). The importance of retention and the impact that missing or deleted data (deleting data collected prior to withdrawal) has on the ability to answer the research question were explained in 6.5% ( n = 6/92) and 5.4% ( n = 5/92) of PILs respectively. Out of the 59 PILs and 58 matching protocols that both communicated plans to use strategies to promote participant retention, 18.6% ( n = 11/59) communicated the same information, the remaining 81.4% ( n = 48/59) of PILs either only partially communicated (45.8%; n = 27/59) the same information or did not communicate the same information (35.6%; n = 21/59) as the protocol with regard to the retention strategy(ies). Conclusion Retention strategies are frequently communicated to potential trial participants in PILs; however, the information provided often differs from the content in the corresponding protocol. Participant retention considerations are best done at the planning stage of the trial and we encourage trial teams to be consistent in the communication of these strategies in both the protocol and PIL.